Analysis of video‐polysomnographic sleep findings in dementia with Lewy bodies. Issue 10 (6th June 2013) - Terzaghi, Michele; Arnaldi, Dario; Rizzetti, Maria Cristina; Minafra, Brigida; Cremascoli, Riccardo; Rustioni, Valter; Zangaglia, Roberta; Pasotti, Chiara; Sinforiani, Elena; Pacchetti, Claudio; Manni, Raffaele
ABSTRACT Knowledge of sleep architecture and disorders of nocturnal sleep in dementia with Lewy bodies (DLB) is limited by a lack of systematic video‐polysomnographic (video‐PSG) investigations. We describe video‐PSG findings in 29 consecutive subjects diagnosed with DLB. All the patients underwent a clinical interview and overnight video‐PSG monitoring. Twenty‐nine nondemented patients with Parkinson's disease (PD) matched for age and sex with the DLB cases were selected for comparison. The DLB subjects showed less 1NREM sleep (P = .000) and more 2NREM sleep (P = .000) than the PD subjects. Sleep apnea (30.7% vs. 34.8%) and periodic limb movements (60.9% versus 50.0%) were frequent in both groups. Disruptive motor behavioral manifestations were more frequent in subjects with DLB (69.6% vs. 26.9%, P = .008) and consisted of not only REM sleep behavior disorder (RBD) but also confusional events (30.3% vs. 3.8%, P = .020) and arousal‐related episodes mimicking RBD. Subjects with DLB in whom a sleep disturbance had been the presenting symptom performed better than those with other onset symptoms on both the Mini–Mental State Examination (22.2 ± 4.1 vs. 18.1 ± 4.6, P = .019) and the Frontal Assessment Battery (15.8 vs. 10.3, P = .010). Polysomnographic findings in DLB show a complex mix of overlapping sleep alterations: impaired sleep structure, sleep comorbidities, and various motor‐behavioral events (not restricted to RBD). Clinicians should be aware of the possibility of misleading symptoms and of the risk of overlooking sleep comorbidities, and consider performing polysomnographic sleep investigations in selected cases. We found evidence that a sleep disturbance as the presenting symptom might indicate a different phenotype of the disease, characterized by milder cognitive impairment. © 2013 International Parkinson and Movement Disorder Society